Ambraziejus Jonynas: the Bibliographic Index, 1937–2019 - Daugirdaitė, Vilma; Pleskačiauskienė, Rūta (Tautosakos darbai, 2022)
This bibliographic index lists all published works by the Lithuanian folklore researcher Ambraziejus Jonynas (1919 02 02 – 2006 07 08), including his books, articles in research publications and encyclopedias, popular academic texts and information published in the dailies and cultural periodicals, compiled and edited publications, series of publications and books, where he was member of the editorial board. Publications about him and his research works are also included. This bibliographic index should help understand and appreciate the Jonynas’ research biography and his role in the Lithuanian folkloristics. In addition, it is an important source for studies of the history of the discipline: the folklorist’s works present vivid illustration of what was relevant during his lifetime. Particularly hard pressure of the Soviet ideology characterized the first decade of Jonynas’ work in the field of folklore research (evident from the titles of the publications). Subsequent decades, during which the researchersʼ self-expression was still rather restricted, saw quite an intense editing of folklore source publications and other compilation works, in which Jonynas’ name also frequently appears: he compiled the publications, edited them or wrote the introductions. His individual research works that are still significant today were published in the late Soviet period. He analyzed interactions between literature and folklore, as well as the Lithuanian folklore historiography. He continued writing on these topics even later, after the restoration of the Lithuanian independence in 1990, giving considerable attention to the biographic facts of Lithuanian folklorists suppressed by the Soviets, and various issues that were important to the Lithuanian folkloristics and its history. Jonynas felt an acute need and wish (or perhaps duty) to contribute to periodicals and cultural press. He used various occasions to introduce folklore collectors and researchers, discuss various issues of folklore survival, preservation, research and promotion. He also saw as his duty to remind of the important facts of the national culture, or at least briefly inform the society of folklorists’ achievements and plans.